Exploring Lived Experiences of Students Studying at Master’s Degree of Online Medical Education Regarding Hidden Curriculum - Shoaleh Bigdeli; Mahboubeh Rastgou Salami; Afsaneh Dehnad; Atefeh Zabihi Zazoly; Zohreh Sohrabi; Zahra Nahardani; John Sandars (Strides in Development of Medical Education, 2023)
Background: The hidden curriculum has a significant role in students’ learning in general and in online learning in particular. However, there are few studies on hidden curriculum of online medical education programs.Objectives: The present study explored master students’ experience of hidden curriculum in an online medical education program.Methods: A phenomenological study was conducted on 12 students of an online medical education master’s degree program at Iran University of Medical Sciences. The results of the semi-structured interviews were analysed by using Colaizzi seven-stage data analysis method.Results: We extracted 6 categories and 12 subcategories from data analysis, depicting the students' experiences of the hidden curriculum. The categories were interactions and communications factors; motivational factors; reflective and interactive feedback; effective teaching and assessing; educational standards, rules, and discipline; faculty member's roles.Conclusion: The findings reflect the hidden messages and factors that constitute the hidden curriculum in the online environment. Constructive interaction and communication, encouragement and reward, and reflective and interactive feedback were the most important aspects defining the hidden curriculum in this learning environment. Therefore, each of the afore-mentioned categories can be considered by educational planners to develop strategies for promoting online learning.